Dual-bionic regenerative microenvironment for peripheral nerve repair - Yanjun Guan; Zhiqi Ren; Boyao Yang; Wenjing Xu; Wenjun Wu; Xiangling Li; Tieyuan Zhang; Dongdong Li; Shengfeng Chen; Jun Bai; Xiangyu Song; Zhibo Jia; et al. (Bioactive Materials, 2023)
Autologous nerve grafting serves is considered the gold standard treatment for peripheral nerve defects; however, limited availability and donor area destruction restrict its widespread clinical application. Although the performance of allogeneic decellularized nerve implants has been explored, challenges such as insufficient human donors have been a major drawback to its clinical use. Tissue-engineered neural regeneration materials have been developed over the years, and researchers have explored strategies to mimic the peripheral neural microenvironment during the design of nerve catheter grafts, namely the extracellular matrix (ECM), which includes mechanical, physical, and biochemical signals that support nerve regeneration. In this study, polycaprolactone/silk fibroin (PCL/SF)-aligned electrospun material was modified with ECM derived from human umbilical cord mesenchymal stem cells (hUMSCs), and a dual-bionic nerve regeneration material was successfully fabricated. The results indicated that the developed biomimetic material had excellent biological properties, providing sufficient anchorage for Schwann cells and subsequent axon regeneration and angiogenesis processes. Moreover, the dual-bionic material exerted a similar effect to that of autologous nerve transplantation in bridging peripheral nerve defects in rats. In conclusion, this study provides a new concept for designing neural regeneration materials, and the prepared dual-bionic repair materials have excellent auxiliary regenerative ability and further preclinical testing is warranted to evaluate its clinical application potential.